(untitled) (PERcursos Linguísticos, 2020)
This article is in the theoretical scope of Text Linguistics in interface with Pragmatics, mainly deals with the phenomenon of recategorization in referencing processes, the contribution of this process to the production of humor and the construction, maintenance and breaking of the face of singer Anitta, on Desciclopédia website. In this way, we seek to demonstrate that the recategorization process is stablished by the junction of verbal and imaginary elements which are responsible for the comic effect given to the character. We also highlight the metaphorical recategorizations, defended by Lima (2013; 2009; 2003) that stands out in explaining the recategorization phenomenon at a higher level of specification. This discussion is supported, theoretically, on studies of Text and Hypertext by Koch and Travaglia (1991); Genette (1997); Koch (2004); Santaella (2013, 2008), Paveau (2017) and Carvalho (2018), in Referencing, Cavalcante (2015; 2013); Lima (2013; 2009; 2003). In addition, in order to contextualize the functions of humor attributed to the character, we adopted the studies by Propp (1992) and in Pragmatics research, Goffman (1981) and Brown and Levinson (1983), among others. The results reveal that the recategorization is the process responsible for the creation of the derogatory humor in the figure of the character Anitta in Desciclopédia page.